From here to diversity: globalization and intercultural dialogues - Centro de Estudos Interculturais (2012)
From Here to Diversity: Globalization and Intercultural Dialogues sees interculturalism as movement, transit, travel, the dynamics between cultures. Contemporary intercultural travel is a global journey, a circumnavigation at the speed of light that underwrites all the comings and goings, the departures and arrivals, the transmissions and receptions that are implicit in this title. Hence, From Here to Diversity examines the motivations, characteristics and implications of cultural interactions in their perpetual movement, devoid of spatial or temporal borders, in a dangerous but stimulating indefinition of limits. In the contemporary intercultural dialogue, new voices are making themselves heard, as valuable sources of study: the voices of women; non-occidentals; the non-powerful; forgotten narratives of a past that was as intercultural as the present (after all, what is colonialism other than a perverse form of interculturality?); global entertainment; tourism; oral literature; diaries; mythical narratives; the cinema; ethnography; new teachings, among so many others. Because this project is also intercultural at its source and subject, From Here to Diversity: Globalization and Intercultural Dialogues adds to the coherence of the project by including contributions from the most wide-ranging backgrounds and nationalities, without fear of the alterity that, after all, we propose to study.